(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This study investigates syntactic economy in English and Uzbek, focusing on word order and sentence structure. Syntactic economy describes a language’s strategy to minimize structural complexity while preserving clarity and communicative effectiveness. English, as an analytic language, relies on a rigid word order and function words to signal grammatical relations, whereas Uzbek, an agglutinative and morphologically rich language, encodes grammatical roles through suffixes and flexible word placement. Despite typological differences, both languages employ economy-driven strategies to ensure efficient and comprehensible communication. Insights from this comparison contribute to understanding linguistic typology, translation practice, and second-language pedagogy